Racionalidade e improvisação nas práticas clínicas em hospitais - Carvalho, Thais Xavier Valente de (2020)
In the quest to improve the quality of services and organizational performance, hospitals adopt clinical protocols in order to systematize care and reduce its variability in their professional practices. However, as rational assumptions implicit in the protocols, they are opposed to the unpredictability inherent in hospital service and, in particular, to clinical practice. In this section, it is common for specialized professionals - to respect the specialization skills conferred - to make use of alternative mechanisms and information, specifically, that is, improvisation - to deal with unforeseen events and surprises during the disorder tests of the patient's clinical condition. This study examines how the clinical staff reconciles rationality and improvisation in clinical practices. The theoretical basis of the study is based on the approach of complex adaptive systems, rationality and organizational improvisation and sensemaking. A qualitative, descriptive and explanatory study had two philanthropic hospitals as an empirical field. The data were collected through ethnographic interviews, document analysis and non-participant observation, by the researcher, as a nursing professional. The data were analyzed through narrative analysis, carried out based on meaning. For the identification of meanings, categories were defined. The analysis revealed the existence of different levels of rationality applicable to the use of protocols in clinical practices in both hospitals. It was found that, although relevant, as clinical practices guided by protocols that are not allowed in view of the unfolding in situations where the clinical picture of patients has unfolded. In this context, he highlighted the importance of improvised practices emerging from doctors and nurses as essential for the success of the team's intervention to solve unforeseen problems. The main conclusion of the study reveals that the practice of clinical practices in patient care depends on the integration of procedures aligned with the protocols that provide safety and professional use, practices with improvisations that arise in emergencies where experience and professional use are present. Thus, understanding the importance of these two aspects becomes strategic for the management of clinical practices and continuous improvement of hospital services provided